Hubungan Pengetahuan dan Sikap Ibu terhadap Pencegahan Stunting di Desa Sei Gelugur - Nurbaiti Nurbaiti; Rahmad Dani; Fahrozy Pradana Putra; Nuroida Afriani; Rs Rabiahtuddinil Adawiyah (MODELING: Jurnal Program Studi PGMI, 2023)
The purpose of this study was to find out how the attitudes and knowledge of mothers related to stunting prevention in Sei Gelugur Village in 2022. In Sei Gelugur Village the correlation (relationship) method was used for research design, and mothers of children aged 6 years and over. below as a research subject. 45 people became the sample size in Sei Gelugur Village which accommodates 450 people. Results Based on the research, most (71.2%) of the research respondents' contributions to stunting prevention were included in the "less" group in terms of knowledge (55.6%). In Sei Gelugur Village in 2022, there is a relationship between the mother's contribution to stunting prevention and the mother's level of understanding about it.